The Influence of Transformational Leadership of Principals and Understanding of Education Reports on Teacher Performance at Langgam District Public High Schools - Masyunila Artati; Fadly Azhar; Neni Hermita (FKIP - Universitas Riau, 2026)
Specifically, the study focuses on three main objectives: to analyze the significant and positive effect of transformational leadership of school principals on teacher performance, to analyze the significant effect of understanding educational report cards on teacher performance, and to analyze the simultaneous effect of transformational leadership of school principals and understanding educational report cards on teacher performance. The study employed a mixed methods approach to obtain both quantitative data and in-depth narratives regarding the experiences of teachers and principals in enhancing teacher performance. Quantitative data were collected through questionnaires distributed to 42 teachers, covering the variables of transformational leadership (X1), understanding of educational report cards (X2), and teacher performance (Y). Data analysis was conducted using descriptive statistics and regression analysis to provide a comprehensive understanding of teacher performance scores, including mean, mode, median, highest, and lowest scores. The results indicated that transformational leadership of school principals had a positive and significant effect on teacher performance with a regression coefficient of 0.312, meaning that each one-unit increase in transformational leadership increases teacher performance by 0.312 units. Descriptive analysis showed that all indicators of transformational leadership were in the very high category, except for one indicator in the high category, with a total mean score of 4.83 (96.5%), reflecting a strong positive influence on teacher performance.